The COVID-19 pandemic and the intertwined care crisis: Evidence of gendered employment effects on informal workers in rural Viet Nam. - Bui, Minh Tam Thi; Bui, Thai Quyen; Nguyen, Tuan Thanh (International Labour Review, 2025)
The article examines the gendered employment effects of the COVID-19 pandemic on informal workers in rural Viet Nam, highlighting the intertwined crises of public health, the economy, and unpaid care work. Using 2021 Vietnamese labour force survey data with a time-use module, the study finds that women, especially female household heads and those in non-farm informal employment, faced greater vulnerability to furloughs, business suspensions, and work hour reductions, while men were more likely to lose jobs outright. The research reveals significant gender disparities in unpaid care work, with rural women spending substantially more hours on domestic and caregiving tasks than men, a burden that intensified alongside adverse employment effects during the pandemic. These findings underscore the need for gender-sensitive policies and increased investment in social care infrastructure in rural Viet Nam to support vulnerable informal workers and promote work–life balance.